The Effect Of Marketing Mix On Purchase Decisions In Zea Zahera Manna Furniture Gallery, Bengkulu Selatan - Wenti Sundari Sundari; Ida Anggriani; M Rahman Febliansa (Penerbit Jurnal Indonesia, 2023)
Customer satisfaction is the most important thing used to attract consumers today. Customer satisfaction is a consumer's feeling of liking or disliking a product after comparing the results of the product with his expectations.The aim of this research is to find out which product, price, promotion and place/location dominantly influence purchasing decisions at the Zea Zahera Manna Furniture Gallery in South Bengkulu. This study uses quantitative research methods, the population in this study is consumers, through a given questionnaire. The technique in taking the research sample using the accidental sampling technique is a technique of determining a sample based on chance, the sample in this study was 45 customers at the Zea Zahera Manna Furniture Gallery, South Bengkulu. Data collection used instruments in the form of questionnaires and the analytical method used was multiple linear regression, determination test and hypothesis testing.Research Results There is a positive and significant influence between products on purchasing decisions at the Zea Zahera Manna furniture gallery in South Bengkulu Regency, which means that the better the product, the more likely it will be to increase purchasing decisions. There is a positive and significant influence between price and purchasing decisions at the Zea Zahera Manna furniture gallery, South Bengkulu Regency, which means that the affordable price of a product will increase purchasing decisions. There is a positive and significant influence between promotion on purchasing decisions at the Zea Zahera Manna furniture gallery, South Bengkulu Regency, which means that the better the promotion is carried out, the purchasing decision will increase. There is a positive and significant influence between place/location on purchasing decisions at the Zea Zahera Manna furniture gallery South Bengkulu Regency, which means that the better the place/location is done, the purchasing decision will increase. There is a positive and significant influence between product, price, promotion and place/location on purchasing decisions at the Zea Zahera Manna furniture gallery, South Bengkulu Regency.